Benzodiazepines and Z-hypnotics consumption in long-COVID-19 patients: Gender differences and associated factors - Carrasco-Garrido, Pilar; Fernández-de-Las-Peñas, Cesar; Hernández-Barrera, Valentín; Palacios-Ceña, Domingo; Jiménez-Trujillo, Isabel; Gallardo-Pino, Carmen (Frontiers in Medicine, 2022)
Background Psychotropic drug consumption has increased during the COVID-19 pandemic. We describe here the prevalence and identifying factors associated with Benzodiazepine (BZD) and Z-hypnotics use among a sample of Spanish adults suffering from long-COVID-19 syndrome, from a gender perspective. Materials and methods Data were anonymously collected between 15th December 2021 and 15th March 2022. The collection form consisted of several questions gathering sociodemographic information, post-COVID symptom, health profile, and pharmacological drug intake. Using logistic multivariate regression models, we estimated the independent effect of each of these variables on self-medicated consumption. Three models were generated (female, male, and both gender). Results Prevalence of BZD and Z-hypnotics use was 44.9% (46.5% for women; 37.8% for men). Zolpidem was the most consumed drug among male (20.7%), and lorazepam in female (31.1%). Patterns of drug consumption among female were related with number of post-COVID symptoms and smoking habit (AOR 2.76, 95%CI 1.16–6.52). Males under 40 years of age are more likely to consume BZD and Z-hypnotics (AOR 5.52, 95%CI 1.08–28.27). Conclusion The prevalence of consumption of BZD and Z-hypnotics in those subjects with long-COVID-19 in our study reaches values of 44.9%. Women with long-COVID-19 declare a higher prevalence of consumption than men. Predictors of BZD and Z-hypnotic in men were, age and number of medication use. Smoking habit and the number of post-COVID symptoms were predictive variables in women.